1962
DOI: 10.2134/agronj1962.00021962005400010010x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Compaction in the Field and Corn Growth1

Abstract: Synopsis Soil compaction markedly reduced growth and yield of corn. Mechanical impedance, as measured by bulk density and needle penetration, was the physical property most highly correlated with the reduction in growth and yield of the corn at each of two fertility levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

1966
1966
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(14 citation statements)
references
References 4 publications
0
13
1
Order By: Relevance
“…There were more roots in the claypan (below 0.25 m) than in the topsoil. Our results vary with those of PHILLIPS and KiRKHAM (1962), who found that maize in Iowa grown in both compacted and non-compacted soil had 89 % or more of its roots in the surface 0.10 m of the soil. In our experiment, roots proliferated below the top 0.10 m. The difference is probably due to moisture.…”
Section: Penetration Resistancecontrasting
confidence: 99%
“…There were more roots in the claypan (below 0.25 m) than in the topsoil. Our results vary with those of PHILLIPS and KiRKHAM (1962), who found that maize in Iowa grown in both compacted and non-compacted soil had 89 % or more of its roots in the surface 0.10 m of the soil. In our experiment, roots proliferated below the top 0.10 m. The difference is probably due to moisture.…”
Section: Penetration Resistancecontrasting
confidence: 99%
“…S EEDBED compaction is usually considered to have an adverse effect on plant growth, as it may limit germination and seedling emergence ( 4,9), retard root development ( 7), restrict aeration ( 4), and in general decrease crop yields ( 1,10). On the other hand, it has been found ( 5,6,8,9,10,13) that under marginal soil moisture conditions a certain degree of compaction may improve germination and seedling emergence. In fact, limited compaction over the seeding row is a common agronomic practice and most seeding implements have attachments for compacting the excessively loose soil that falls over the seeds.…”
mentioning
confidence: 99%
“…Soil moisture and temperature have the ability to promote or delay seed germination and plant emergence Schneider and Gupta, 1985). Plant growth and development requires a soil condition that has adequate soil moisture and minimal root penetration resistance (Phillips and Kirkham, 1962). Therefore, quantifying the affects of tillage systems on soil moisture, temperature, and compaction can help account for differences in plant growth and development.…”
Section: Resultsmentioning
confidence: 99%
“…Penetration resistance is a common measure of soil strength, where increased penetration resistance restricts root growth (Singh et al, 1992;Taylor and Ratliff, 1969;Voorhees et al, 1975). Therefore, penetration resistance is attributed to a reduction of crop growth and yield (Croissant et al, 1991;Phillips and Kirkham, 1962). In a three year study, Croissant et al (1991) determined compacted notillage treatments reduced dry bean (Phaseolus vulgaris L.) yields by 26% over noncompacted treatments.…”
Section: Resultsmentioning
confidence: 99%